Inovasi Pembuatan Pagar Taman Dari Kayu dan Daur Ulang Botol Bekas di Universitas Sunan Giri Surabaya - Moch. Reno; Dwi Sriwidadi; Moch. Fairuz Fahrezi Al Haibah; Salwa Sabrina; Arif Rachman Putra; Didit Darmawan; Cilda Thesissa Dzinnur; Muhammad Yusron Maulana El-Yunusi; Rommy Hardyansah; Muchamad Catur Rizky (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to design and build a garden fence made of wood and recycled bottles in an effort to develop an environmentally friendly and cost-effective solution. In addition to functioning as a room divider, this garden fence can also be used as a decorative component to add to the aesthetic appeal of the garden. This study examines the structural strength, material durability, and aesthetic value of the fence building using wood and recycled bottles. The method used in this activity is the ABCD method, the ABCD (Asset Based Community Development) approach method which is a mentoring method that prioritizes the utilization of assets and potentials around the community. This research method also evaluates the environmental impact and cost efficiency of using recycled materials. The results of the study show that a fence made of wood and recycled bottles can be a practical and attractive choice for a garden plan. This fence not only supports the management of plastic bottle waste, but also provides a smart solution that is financially efficient and affordable.